PERAN KEPEMIMPINAN JAWA (Studi Eksplorasi pada CV Batik Indah Rara Djonggrang Yogyakarta) - Nur Rahman, Dani; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2012)
This study aimed to know the role of Javanese leadership in the Java company, which was owned by the leader and employee. The purpose of this research was to know the understanding and view of the owner of the company to Javanese leadership. Starts from identifying leader and employee perception on the practice leadership based on the values in the Javanese culture. Javanese culture which was the root of the Java society, had a big part in the character building of the leader in Indonesia. The practice leadership based on the value in th Javanese culture become an integral part in the Javanese leadership practice in company. This study uses qualitative methods in which data collection was the role of Javanese leadership. The sample in this study were workers have work experience of minimal 10 years at CV Batik Indah Rara Djonggrang Yogyakarta. Results obtained from this study states that of the five elements of Javanese cultue that is gotong royong, rukun, bisa rumangsa, sepi ing pamrih rame ing gawe, aja dumeh already reflects the role of Javanese culture in the CV Batik Indah Rara Djonggrang Yogyakarta.